Effects of Bacterial Supplementation on Black Soldier Fly Growth and Development at Benchtop and Industrial Scale - Kooienga, Emilia M.; Baugher, Courtney; Currin, Morgan; Tomberlin, Jeffery K.; Jordan, Heather R. (Frontiers in Microbiology, 2020)
Historically, research examining the use of microbes as a means to optimize black soldier fly growth has explored few taxa. Furthermore, previous research has been done at the benchtop scale, and extrapolating these numbers to industrial scale is questionable. The objectives of this study were to explore the impact of microbes as supplements in larval diets on growth and production of the black soldier fly. Three experiments were conducted to measure the impact of the following on black soldier fly life-history traits on 1) Arthrobacter AK19 supplementation at benchtop scale, 2) Bifidobacterium breve supplementation at benchtop scale, and 3) Arthrobacter AK19 and Rhodococcus rhodochrous 21198 as separate supplements at an industrial scale. Maximum weight, time to maximum weight, growth rate, conversion level of diet to insect biomass, and associated microbial community structure and function were assessed for treatments in comparison to a control. Supplementation with Arthrobacter AK19 at benchtop scale enhanced growth rate by double at select time points and waste conversion by approximately 25-30% with no impact on the microbial community. Predicted gene expression in microbes from Arthrobacter AK19 treatment were enriched for functions involved in protein digestion and absorption. Bifidobacterium breve, on the other hand, had the inverse effect with larvae being 50% less in final weight, experiencing 20% less conversion, and experienced suppression of microbial community diversity. For those tested at the industrial scale, Arthrobacter AK19 and R. rhodochrous 21198 did not impact larval growth differently as both resulted in approximately 22% or more greater growth than those in the control. Waste conversion with the bacteria was similar to that recorded for the control. And, diets treated with the supplemental bacteria showed increased percent difference in predicted genes compared to control samples for functions involved in nutritional assimilation (e.g., protein digestion and absorption, energy metabolism, lipid metabolism). Through these studies, it was demonstrated that benchtop and industrial scale results can differ. Furthermore, select microbes can be used at an industrial scale for optimizing black soldier fly larval production and waste conversion, while others cannot. Thus, targeted microbes for such practices should be evaluated prior to implementation.